2020
DOI: 10.2217/fmb-2019-0085
|View full text |Cite
|
Sign up to set email alerts
|

Novel Isoniazid Derivative as Promising Antituberculosis Agent

Abstract: Background: A major focus of tuberculosis drug discovery is aimed at the development of novel antibiotics with activity against drug-resistant strains of Mycobacterium tuberculosis. Results: We have synthesized ten isoniazid derivatives and investigated for antibacterial activity toward M. tuberculosis H37Rv and isoniazid-resistant strain SRI 1369. It was revealed that only one compound – isonicotinic acid (1-methyl-1H-pyrrol-2-ylmethylene)-hydrazide (1) is active toward isoniazid-resistant strain with minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…MRC-cell (normal human fetal lung fibroblasts) was selected because it is widely used for the phenotypic screening of compounds and J774A.1, a mice macrophage original cell line. This cell is usually used to determine the inhibition of intracellular pathogens and, because of the incubation time of the intramacrophagic experiment, it was tested for up to 72 h [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…MRC-cell (normal human fetal lung fibroblasts) was selected because it is widely used for the phenotypic screening of compounds and J774A.1, a mice macrophage original cell line. This cell is usually used to determine the inhibition of intracellular pathogens and, because of the incubation time of the intramacrophagic experiment, it was tested for up to 72 h [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compound 1-methyl-1H-pyrrol-2-ylmethylene)-hydrazide (90) (Fig. 25 ) has shown inhibitory activity toward isoniazid-resistant strain with IC 50 of 0.14 μM [ 161 ]. Shiva Raju et al [ 162 ] also reported 1 H -pyrrolo[2,3-d]pyrimidine-1,2,3-triazole analogs as novel anti-tubercular agents.…”
Section: Antimycobacterial Agentsmentioning
confidence: 99%
“…Among the series, compounds 3a-f, 4, 5 and 6 were found active showing sensitivity towards growth inhibition of H37Rv strain of M. tb [9]. A series of isoniazid derivatives were synthesized evaluated for anti-TB activity against the drug resistant strains of M. Tb by Volynets et. al.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds were found to be active with the MIC values ranging 0.4-42 µM. Among the series the most active compound 7 showed MIC = 0.4 µM against virulent strain (H37Rv) whereas MIC = 0.14 µM against INH-Resistant strain [20]. Patil et.…”
Section: Introductionmentioning
confidence: 99%